Of Love & Life : Cocktails for Three / Angel Falls / A Place in the Hills - Wickham, Madeleine; Hannah, Kristin; Paver, Michelle (London The Reader's Digest Association Ltd.)
Cocktails for Three / Angel Falls / A Place in the Hills.
Three Novels Selected and Condensed by Reader's Digest.
Keywords: Romance fiction, English -- English fiction -- Romance fiction -- Psychological fiction